Coinfection with Cryptococcus Gattii and Mycobacterium Tuberculosis in an Otherwise Healthy 18-Year-Old Woman - Lindsay Van Tongeren; Tawimas Shaipanich; John A Fleetham (Canadian Respiratory Journal)
A case of Cryptococcus gattii (pulmonary and central nervous system) and Mycobacterium tuberculosis (pulmonary) coinfection in an otherwise healthy young woman is reported. The patient presented with a two-month history of dry cough. She had an unremarkable medical history. Both tuberculosis and cryptococcosis were diagnosed following bronchoscopy, and a subsequent lumbar puncture revealed C gattii in the cerebrospinal fluid. There is evidence that both M tuberculosis and C gattii may have suppressive effects on the host immune system. This suggests a mechanism by which an otherwise healthy individual developed these two infections.